Adopting global tools for the advancement of pharmacy practice and workforce in Saudi Arabia - Dalia Almaghaslah; Asmaa Al-Haqan; Ahmed Al-jedai; Abdulrhman Alsayari (Saudi Pharmaceutical Journal, 2022)
Background: The continuing expansion of the pharmacist’s role necessitates continuous evaluation of current practice to identify strategies for improvements. The International Pharmaceutical Federation (FIP) has developed tools to support stakeholders in identifying development needs and planning advancement strategies. The aim of this research was to utilise the FIP Global Competency Framework, version 2 (GbCF v2), and FIP Development Goals (DGs) to evaluate competencies related to pharmacy practice in Saudi Arabia, and to understand the strategies needed to develop and improve the current practice. Methods: The study involved four phases. Phase 1 involved translation of the FIP GbCF v2 into the Arabic language. Phase 2 was a consensus panel validation to establish the initial relevance of the competencies to current practice. Phase 3 included a national survey distributed to all registered pharmacists in Saudi Arabia. The final phase was conducted through mapping ‘not relevant’ competencies to FIP DGs to identify priorities. Results: The translation phase yielded a bilingual framework that could be utilized by pharmacists in Saudi Arabia. The initial validation phase identified 61 behavioral statements (from 124 in the GbCF v2) as ‘highly relevant’ or ‘relevant’ to pharmacy practice. Findings from the national survey identified a list of ‘not relevant’ competencies that could highlight gaps in current practice. The final mapping phase generated a list of three FIP DG priorities: DG5 (competency development), DG8 (working with others) and DG11 (impact and outcomes). Conclusion: The study indicated that competencies in the GbCF v2 were relevant to pharmacists practicing in the country. However, some competencies were perceived as ‘not relevant’ to current practice and these highlighted gaps in the current practice that need attention. Mapping ‘not relevant’ competencies to FIP DGs should be used as a starting point towards developing strategies, systems, and protocols to advance pharmacy practice in Saudi Arabia.